Postoperative oxygenation in healthy dogs following mechanical ventilation with fractions of inspired oxygen of 0.4 or >0.9. (May 2020) - Martin-Flores, Manuel; Cannarozzo, Cheyenne J.; Tseng, Chia T.; Lorenzutti, Augusto M.; Araos, Joaquin D.; Harvey, H. Jay; Gleed, Robin D.; Campoy, Luis
Abstract: Objective: To evaluate arterial oxygenation during the first 4 postoperative hours in dogs administered different fractions of inspired oxygen (Fi O2 ) during general anesthesia with mechanical ventilation. Study design: Prospective, randomized clinical trial. Animals: A total of 20 healthy female dogs, weighing >15 kg and body condition scores 3–7/9, admitted for ovariohysterectomy. Methods: Dogs were randomized to breathe an Fi O2 >0.9 or 0.4 during isoflurane anesthesia with intermittent positive pressure ventilation. The intraoperative PaO2 :Fi O2 ratio was recorded during closure of the linea alba . Arterial blood was obtained 5, 60 and 240 minutes after extubation for measurement of PaO2 and PaCO2 (Fi O2 = 0.21). Demographic characteristics, duration of anesthesia, PaO2 :Fi O2 ratio and anesthetic agents were compared between groups with Wilcoxon tests. The postoperative PaO2, PaCO2, rectal temperature, a visual sedation score and events of hypoxemia (PaO2 < 80 mmHg) were compared between groups with mixed-effects models or generalized linear mixed models. Results: Groups were indistinguishable by demographic characteristics, duration of anesthesia, anesthetic agents administered and intraoperative PaO2 :Fi O2 ratio (all p > 0.08). Postoperative PaO2, PaCO2, rectal temperature or sedation score were not different between groups (all p > 0.07). During the first 4 postoperative hours, hypoxemia occurred in three and seven dogs that breathed Fi O2 >0.9 or 0.4 during anesthesia, respectively ( p = 0.04). Conclusions and clinical relevance: The results identified no advantage to decreasing Fi O2 to 0.4 during anesthesia with mechanical ventilation with respect to postoperative oxygenation. Moreover, the incidence of hypoxemia in the first 4 hours after anesthesia was higher in these dogs than in dogs breathing Fi O2 >0.9.